Análisis de la participación ciudadana en la gestión pública del Gobierno Autónomo Descentralizado del cantón Tosagua del periodo 2021-2022 - Conforme Torres, María Yaritza (2024)
The purpose of this Curricular Integration Work was to analyze the advances of citizen participation in public management for improvement in the Decentralized Autonomous Government of the Tosagua canton. To achieve this, various stages and activities focused on the specific objectives of the study were carried out. Data collection techniques such as interviews and surveys were used, as well as various methods. In addition, bibliographic and field research was carried out, and all the theoretical sources that support each of its phases were explored. In the results obtained, it is highlighted that within the GAD there are several participation mechanisms such as local assemblies at all levels of government, participatory budgets that allow the community to influence budget decisions, public hearings and popular councils, the empty chair as a representation of absent in debates, observatories to monitor relevant issues, citizen oversight to monitor compliance with commitments and prior consultations to protect the rights of indigenous peoples. In addition, accountability and access to public information are promoted, as well as the institution facing problems that result in citizen dissatisfaction both in the way in which they exercise their right to participate, the low perception of suitability of the mechanisms and activities that are developed, the communication channels that are used to make them known, as well as the disagreement with the administrative decisions that are made in this regard.